Fuzzy logic methods in assessing the transport and warehouse complexes functioning quality (Nexo Revista Científica, 2021)
In most sectors of the national economy, technical facilities are represented by unloading devices that extract bulk cargo from the freight rolling stock, store it for a certain time, and ship it to a similar or other type of transport. Objects intended for the implementation of the stages of loading, unloading, and various storage periods, including bulk cargos, are commonly referred to by the broad scientific community as transport and warehouse complexes (TWC). Most operations performed in the TWC are the movement of goods (internal movements, receiving or sending goods by various modes of transport. The authors clarified the concept of "transport and warehouse complex" - it is an element of the transport network of the region, providing communication of external transport systems of the regions and performing the functions of converting the cargo flow of the region into the cargo flow sent by the region. On the one hand, they perform functions of transshipment points in relation to deep (economic) warehouses, and on the other – the functions of storage facilities. Their primary purpose is determined and depends on a large number of factors, including: the size of the direct service area, the ratio of the design capacity of the warehouse to the volumes of deliveries and the use of bulk cargo, as well as the condition of roads in the serviced area, the uniformity of the receipt of bulk cargo and the availability of vehicles for their delivery to the consumer.